2023
DOI: 10.1057/s41599-023-02273-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spiritual leadership on proactive customer service performance: The roles of psychological empowerment and power distance

Delong Zhu,
Waseem Bahadur,
Muhammad Ali

Abstract: Scholars have consistently demonstrated that spiritual leadership yields positive outcomes for employees. However, it is not clear how spiritual leadership influences proactive customer service performance. The purpose of this research is to develop a model, grounded in social cognitive theory, to identify why and when spiritual leadership promotes proactive customer service performance. Specifically, the focus is on how spiritual leadership through employee psychological empowerment facilitates proactive cust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…As stated by (Karim et al, n.d.), spiritual leadership plays a vital role in the dynamic workplace of the 21st century. The concept encompasses attitudes, values, and behaviors that might inspire individuals and others to cultivate spiritual resilience by fostering a feeling of purpose and unity (Binu Raj et al, 2023b) According to (Zhu et al, 2023) spiritual leadership can boost organizational performance by enhancing the physical health and well-being of personnel. Research indicates that spiritual leadership has a vital role in enhancing productivity and achieving positive outcomes at the unit level, which includes improving staff performance (Maryati, 2019).…”
Section: Results Participants' Demographicmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated by (Karim et al, n.d.), spiritual leadership plays a vital role in the dynamic workplace of the 21st century. The concept encompasses attitudes, values, and behaviors that might inspire individuals and others to cultivate spiritual resilience by fostering a feeling of purpose and unity (Binu Raj et al, 2023b) According to (Zhu et al, 2023) spiritual leadership can boost organizational performance by enhancing the physical health and well-being of personnel. Research indicates that spiritual leadership has a vital role in enhancing productivity and achieving positive outcomes at the unit level, which includes improving staff performance (Maryati, 2019).…”
Section: Results Participants' Demographicmentioning
confidence: 99%
“…In the field of education, teachers play a central role in the educational process, which extends beyond intellectual capacity to encompass attitudes, behaviors, and normative values beyond explicitly stated job descriptions (Zhu et al, 2023). This is influenced by the spirituality and motivation of teachers in their work.…”
Section: Introductionmentioning
confidence: 99%
“…It might be due to the larger pitch and bevel angle of the Blade-B3 cutter bar [55][56][57][58][59] . Wang et al 54 also reported that with an increase in the pitch of the blade, the cutting force increased 37,38,[60][61][62][63][64][65][66][67][68][69][70][71] . The power requirement was increased with the increase in cutter bar speed.…”
Section: Discussionmentioning
confidence: 99%